1998
DOI: 10.3109/03005364000000090
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Body Temperature on Transient Evoked Otoacoustic Emissions

Abstract: Thirty patients undergoing open heart surgery under induced hypothermia had transient evoked otoacoustic emissions (TEOAE) recorded during cooling to 26.07 degrees C (standard deviation (SD) 4.25 degrees C) vesically measured temperature and 24.86 degrees C (SD 4.7 degrees C) nasopharyngeally measured temperature respectively. Subsequently tè patients were rewarmed until normal body temperature was reached again. There was a clear influence of body temperature on the amplitudes and reproducibilities of the TEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…There are small differences in body temperature between males and females, and temperature has been shown to affect OAEs (e.g., Seifert et al, 1998). Might this physiological difference be responsible for producing some of the sex and group differences reported above?…”
Section: Other Possible Causal or Contributing Factorsmentioning
confidence: 99%
“…There are small differences in body temperature between males and females, and temperature has been shown to affect OAEs (e.g., Seifert et al, 1998). Might this physiological difference be responsible for producing some of the sex and group differences reported above?…”
Section: Other Possible Causal or Contributing Factorsmentioning
confidence: 99%
“…Le Bourgeois III et al 29 , using animal models and looking at tympanic perforations of various sizes, were only able to find changes to DPOAE when perilymph fistulae were present. Therefore, although it may be said that changes in middle ear impedance during hypothermia could hinder DPOAE recording, we tend to agree with Seifert et al 11 and Kvolves et al 10 and conclude that OAE disappearance during hypothermia does not occur by the works of such mechanism.…”
Section: Discussionmentioning
confidence: 42%
“…We found studies on the impact hypothermia has on recording evoked transient OAE in humans 11 , but not DPOAEs. We believe that our study has clearly demonstrated the impact hypothermia has upon DPOAE based on the comparison between the PRE and HYPOTHERMIA data series, where a statistically significant amplitude reduction was identified for all points in the 'DPgram' deemed valid (F5, F6, F7, F8, F9, F10, F11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] ABR and otoacoustic emission (OAE) amplitudes decrease and ultimately disappear with a lowering of temperature. 16,17 Cooling may also decrease middle ear compliance. 18 In heart patients, ABRs and OAEs return to normal upon rewarming.…”
mentioning
confidence: 99%